The equation of the tangent line to the curve is y = -2.
Given,
[tex]y^{2} (y^{2} -4)= x^{2} (x^{2} -5)[/tex]
On solving the above equation, we get
[tex]y^{4} - 4y^{2}=x^{4}-5x^{2}[/tex]
Differentiate with respect to x.
[tex]4y^{3} y^{'} -8yy^{'}=4x^{3}-10x[/tex]
[tex]y^{'}(4y^{3}-8y )=4x^{3} -10x[/tex]
[tex]y^{'} = \frac{4x^{3}-10x }{4y^{3}-8y }[/tex]
To find the slope of the tangent line at (0,-2) plug x = 0 and y = -2 into the [tex]y^{'}[/tex].
[tex]y^{'} = \frac{0}{-16}[/tex]
Hence,
The slope is 0 and therefore a horizontal line with a y value of -2, i.e. y = -2.
The equation of the tangent line to the curve is y = -2.
Learn more about Implicit Differentiation here
https://brainly.com/question/11887805
#SPJ4